2008
DOI: 10.1108/02634500810860638
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of self‐congruity, attitudes and customer satisfaction on customer behavioural intentions in retail environment

Abstract: Purpose -This paper aims to develop a model that will include self-image congruence, attitudes, satisfaction and explain their role on behavioural intentions. Design/methodology/approach -A qualitative survey was carried out. It was followed by a quantitative study, conducted in two stages to clarify the self-congruity scale. Results were used to lead an exploratory investigation of a conceptual model of behavioural intentions. Findings -Ideal self-image congruity had a stronger direct effect on attitudes, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 72 publications
5
55
0
Order By: Relevance
“…Cronin, Brady and Hult [44], Vilares and Coelho [45], Lai and Chen [46], Anderson and Mittal [47], Ibrahim and Najjar [48], Szymanski and Henard [49]. Satisfaction is therefore regarded as a significant determinant of behavioural intentions according to Bearden and Teel [50] and Ibrahim and Najjar [48].…”
Section: Behavioural Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cronin, Brady and Hult [44], Vilares and Coelho [45], Lai and Chen [46], Anderson and Mittal [47], Ibrahim and Najjar [48], Szymanski and Henard [49]. Satisfaction is therefore regarded as a significant determinant of behavioural intentions according to Bearden and Teel [50] and Ibrahim and Najjar [48].…”
Section: Behavioural Intentionsmentioning
confidence: 99%
“…A primary concern to an organisation should be the behavioural intentions of its customers [40,41]. Both quality and satisfaction have drawn the attention of researchers due to their linkage to customer loyalty.…”
Section: Behavioural Intentionsmentioning
confidence: 99%
“…Customer is presumed to be one of the most important stakeholders in any organisation because without him, organisations are not likely to succeed. Hence, customer behavioural intention is one of the main concepts that have been studied in the marketing literature (Ibrahim and Najjar, 2008). It is presumed that the knowledge regarding consumer behaviour will go a long way in ensuring effective marketing policies in favour of customers which will eventually facilitates positive customer attitude towards the organisations, more especially as customer behavioural intention is a strong indication of his actual behaviour (Francis et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge regarding actual purchase will help researchers understand the needs and wants of customers. Thus, the data obtained from the actual purchase can help to identify the marketing strategy (Kim & Chung, 2011), customer satisfaction, and to ensure the continuity of the business (Carneiro et al, 2005;Ibrahim & Najjar, 2008;Paul & Rana, 2012). Certain studies found that actual purchase is complex and vary by segment (Chiang et al, 2010;Shafiq et al, 2011).…”
Section: Actual Purchasementioning
confidence: 99%
“…Adverse effect occurs due to the existence of poison found in herbal plants, pollution, and poor manufacturing practice (Balammal et al, 2012;Saad et al, 2006). These issues will affect the actual purchase of herbal products, by understanding that the buying pattern will help entrepreneurs in determining an effective marketing strategy (Kim & Chung, 2011) and also to ensure the continuity of business sustainability (Carneiro et al, 2005;Ibrahim & Najjar, 2008;Paul & Rana, 2012).…”
Section: Introductionmentioning
confidence: 99%